Starch Based Biocomposite from Sago (Metroxylon sagu) with Nano-Chitosan reinforcement : Mechanical and Thermal Characteristics - Athoillah Azadi; Sugeng Supriyadi; Heny Herawati (Chemistry Department, The University of Brawijaya, 2020)
A biocomposite system incorporating sago starch and nano-chitosan (SS/NCS) were developed by casting and solvent evaporation method. The purpose of this experiment for characterization of the film based on sago starch (SS) with a variation of the addition of nano-chitosan (0, 2, 4, 6 and 8% by weight starch) and analyze its effect on mechanical properties, thermal properties, and morphological characteristics of mixed film (SS / NCS). Possible intermolecular interactions between SS and NCS were confirmed by Fourier-transform infrared spectroscopy (FTIR) and the reduction of crystallinity in XRD. The experimental data showed that the incorporation of nano-chitosan resulted in an increase in film solubility, tensile strength and elongation at break and a decrease in Young’s modulus. Elongation at break of the (SS/NCS) films increased with increasing of nano-chitosan concentration. The water vapor permeability (WVP) of (SS/NCS) films increased with an increase of chitosan concentration and the same tendency observed for the moisture content. Based on thermogravimetric analysis (TGA), the percentage of nano-chitosan content in starch-based films can increase thermal stability.. Scanning electron microscope (SEM) shows the surface morphology and interface of NCS/SS composite films and suggests sufficient homogenization of starch and chitosan in biodegradable composite films.